Sex hormone manipulation slows reaction time and increases labile mood in healthy women. (June 2016) - Stenbæk, D.S.; Fisher, P.M.; Budtz-Jørgensen, E.; Pinborg, A.; Hjordt, L.V.; Jensen, P.S.; Knudsen, G.M.; Frokjaer, V.G.
Highlights: Sex hormone manipulation increases reaction time compared to placebo. Sex hormone manipulation increases labile mood in a subgroup of vulnerable women. Early phase hypogonadism does not alter verbal affective memory recall. Early phase hypogonadism does not trigger self-reported mental distress. Abstract: Background: Women show increased risk of depressive symptoms in life phases where ovarian steroid hormone levels fluctuate or decline rapidly. The risk mechanisms may include changes in mental state and affective cognition possibly mediated by serotonergic neurotransmission. Methods: In a randomized controlled double-blinded trial, 61 healthy women (mean age 24.3 ± 4.9 years) were tested with measures of affective verbal memory, reaction time, mental distress, and serotonin transporter binding at baseline and at follow-up after receiving gonadotropin-releasing hormone agonist (GnRHa) or placebo intervention. Women also reported daily mood profiles during intervention. We tested direct effects of intervention and indirect effects through changes in serotonin transporter binding on verbal affective memory, simple reaction time and self-reported measures of mental distress, and further effects of GnRHa on daily mood. Results: GnRHa induced an increase in simple reaction time ( p  = 0.03) and more pronounced fluctuations in daily self-reported mood in a manner dependent on baseline mood ( p  = 0.003). Verbal affective memory recall, overall self-perceived mental distress, and serotonin transporter binding were not affected. Conclusions: In healthy women transient sex-steroid hormone fluctuations decrease speed of information processing and further produce more labile mood only in women with elevated levels of mood disturbances at baseline.